General characteristics of UPV women who watch sports on TV. - Zamar, Ellen Ruth
This paper is a descriptive study of the general characteristics of UPV women who watch sports program on television. A total of 100 questionnaires were given out to 100 women respondents. The study was conducted at the University of the Philippines in the Visayas campus., The answers were recorded and tallied and tables were used to analyze the results of the survey. The researcher made use of the coding methods, that is with the use of the code book and the code sheet. The results indicated that women who watch sports on TV are athletic, sports minded, will-rounded and aggressive individuals. The researcher chose to get the characteristics of women only because she believes that the topic has received little attention and she realizes that women have roles to play in the popularity of sports in our world today. The respondents chosen for this survey were chosen randomly with the assumption that all of them watch programs on television . Respondents from different courses were chosen with ages ranging from 16 to 22 years old. The subjects were all college students from the first to fourth year college. They were asked to answer the questions as honestly as they could so that this research study would be valid.